Accounting students' and instructors' perceptions on effective teaching methods and instructor characterictics: a Somalian study /cby Abbas Ismail Addow - Addow, Abbas Ismail (Kulliyyah of Economics an Management Sciences, International Islamic University Malaysia, 2011)
Based on the importance of teaching methods and lecturers characteristics in academic institutions, the main objective of this study is to examine accounting students' and their instructors' perceptions of effective teaching methods and instructors characteristics and to investigate if there is difference in perceptions between them. The study also explores if there is a difference in perceptions based on gender. The sample of this exploratory study comprises the final year accounting students and their lecturers in two Somalian universities. Total respondents of this study are 245 students and 62 lecturers. Descriptive and two-sample t-test analyses were conducted on this study to achieve the objectives of the survey. The results indicate that students and their lecturers perceive in-class activities as more important than outside assignments. The findings similarly indicate that students perceive in-class approach to teaching as being most effective. The instructor characteristics that is most valued by students is the capability of the lecturers to encourage students to develop them in critical thinking ability. The findings also suggest that a few differences in perceptions exist between students and lecturers and based on genders. The study has several implications. First, it contributes to the literature on accounting students' and lecturers' perceptions of effective teaching methods and instructors characteristics. Second, the study provides insights into ways to make the teaching of accounting more effective. Finally, it is hoped that the study will be able to assist in the formulation of guidelines for the effective teaching of accounting, particularly in Somalia.